2019
DOI: 10.1177/1040638719831340
|View full text |Cite
|
Sign up to set email alerts
|

Analytical validation of fecal 3-bromotyrosine concentrations in healthy dogs and dogs with chronic enteropathy

Abstract: Studies that have used serum 3-bromotyrosine (3-BrY) to investigate eosinophil activation in dogs have found elevated 3-BrY levels in clinical patients with chronic enteropathy (CE). To our knowledge, a method to measure 3-BrY concentrations in feces has not been reported. We developed and analytically validated an electron ionization gas chromatography-mass spectrometry method to measure fecal 3-BrY concentrations in dogs. The mean and maximum fecal 3-BrY concentrations in healthy dogs (n = 40) and dogs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Nevertheless, the focus of this analysis is on feces, as reports have evidenced that the assessment of 3-BrY concentrations in fecal samples reflect the level of eosinophil activation in the GI tract more accurately than serum biomarkers (Sattasathuchana et al, 2019). A recent study revealed higher concentrations of fecal 3-BrY concentrations in dogs with CIE; however, sensitivity and specificity to differentiate between the different forms of CIE are yet to be determined (Sattasathuchana et al, 2019). Sattasathuchana et al (2015Sattasathuchana et al ( , 2017 assessed 3-BrY concentrations in the serum of dogs with CIE.…”
Section: Fecal and Urinary Biomarkersmentioning
confidence: 99%
“…Nevertheless, the focus of this analysis is on feces, as reports have evidenced that the assessment of 3-BrY concentrations in fecal samples reflect the level of eosinophil activation in the GI tract more accurately than serum biomarkers (Sattasathuchana et al, 2019). A recent study revealed higher concentrations of fecal 3-BrY concentrations in dogs with CIE; however, sensitivity and specificity to differentiate between the different forms of CIE are yet to be determined (Sattasathuchana et al, 2019). Sattasathuchana et al (2015Sattasathuchana et al ( , 2017 assessed 3-BrY concentrations in the serum of dogs with CIE.…”
Section: Fecal and Urinary Biomarkersmentioning
confidence: 99%
“…The concentrations of 3-BrY in serum and fecal samples were measured using stable isotope dilution and electron ionization gas chromatography/mass spectrometry, with synthetic deuterated-BrY (D3-bromotyrosine) as the internal standard, as previously described [11,12,19]. A reference interval for canine serum 3-BrY concentration was previously established as ≤0.6 µmol/L based on samples from 41 healthy dogs [11,12,19].…”
Section: Measurement Of Serum and Fecal 3-bry Concentrationsmentioning
confidence: 99%
“…Lymphocytic-plasmacytic gastroenteritis and eosinophilic gastroenteritis are the two most common histological findings in dogs with CIE, whereas other inflammatory cell types such as neutrophils, monocytes, and macrophages are less frequently identified [2,3,6]. Multiple biomarkers for CIE have been developed and evaluated for assessing organ function, disease activity and severity, and disease outcome [1,3,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations